2020
DOI: 10.1186/s13059-020-02172-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an eutherian gene cluster generated after transposon domestication identifies Bex3 as relevant for advanced neurological functions

Abstract: Background One of the most unusual sources of phylogenetically restricted genes is the molecular domestication of transposable elements into a host genome as functional genes. Although these kinds of events are sometimes at the core of key macroevolutionary changes, their origin and organismal function are generally poorly understood. Results Here, we identify several previously unreported transposable element domestication events in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 121 publications
0
12
0
2
Order By: Relevance
“…We confirmed that GFP-TCEAL4 predominantly localises in the nucleus of U2OS cells (Supplementary Figure S6E) and thus may potentially be involved in nuclear processes such as transcription. However, no TCEAL4 functions have yet been described, and the related BEX proteins are suggested to be hubs that participate in multiple cellular pathways 37 . To investigate further, we immunoprecipitated GFP-TCEAL4 for mass spectrometry (Figure 4A, Supplementary Table 2) and identified several hundred interacting proteins, substantially increasing the list of TCEAL4 interactors collated from high-throughput studies (Figure 4B).…”
Section: Resultsmentioning
confidence: 99%
“…We confirmed that GFP-TCEAL4 predominantly localises in the nucleus of U2OS cells (Supplementary Figure S6E) and thus may potentially be involved in nuclear processes such as transcription. However, no TCEAL4 functions have yet been described, and the related BEX proteins are suggested to be hubs that participate in multiple cellular pathways 37 . To investigate further, we immunoprecipitated GFP-TCEAL4 for mass spectrometry (Figure 4A, Supplementary Table 2) and identified several hundred interacting proteins, substantially increasing the list of TCEAL4 interactors collated from high-throughput studies (Figure 4B).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding their expression, according to the available data from adult organs, most genes present a tissue-enriched pattern, with the brain be the organ showing the highest expression levels in most of the paralogs. Navas-Pérez et al (2020) also reported an analysis of the expression via in situ hybridization during mouse development, where they observed that especially the Bex genes were highly and widely expressed with Bex3 strongly expressed in the nervous system.…”
Section: A Whole New Cluster From a Domesticated Transposable Element: Impact Into The Evolution Of The Eutherian Brainmentioning
confidence: 99%
“…Thus, Bex3 would be fine-tuning the regulation of the mTOR pathway and its deregulation was suggested to be related to autism spectrum disorder in humans (Ganesan et al, 2019). Some of the structural features present in BEX and TCEAL families have been detected in the ancestral transposon HAL1b (Navas-Pérez et al, 2020), which indicates that they were preserved along the domestication process., and a positive selection signature can be found in particular cases, suggesting than ancestral genes went through an adaptative process before the diversification of placental mammals. The differences in the neocortex complexity between eutherian and non-eutherian mammals (Cheung et al, 2010) may thus be linked to genomic novelties that emerged during this transition affecting neural development, and maybe, to the appearance of the Bex/Tceal cluster.…”
Section: A Whole New Cluster From a Domesticated Transposable Element: Impact Into The Evolution Of The Eutherian Brainmentioning
confidence: 99%
See 2 more Smart Citations